2022
DOI: 10.1111/nuf.12762
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and prioritization of strategies to improve clinical reasoning skills among coronary care nurses: A qualitative study

Abstract: Introduction Clinical reasoning (CR) is the most important competency for safe and quality care delivery in coronary care unit (CCU). Nonetheless, evidence shows that nurses in CCU do not have the necessary CR skills to manage challenging situations and provide quality care in these units. Identifying the possible strategies for CR skill improvement is a key step in improving nurses' CR skills. Aim The aim of the study was to explore and prioritize strategies for CR skill improvement among nurses in CCU. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Several studies pinpointed significant dimensions that nurses rated as most influential for cultivating their professional knowledge and skills; Hosseinzadeh et al. 45 reported that medical professional interaction and communication was an instrumental ability for achieving nursing competency and frequently coexisted with insufficient PSE. Better communication skills confer greater PSE among nurses, likely resulting from increased confidence in providing care and constructing positive interpersonal relationships with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies pinpointed significant dimensions that nurses rated as most influential for cultivating their professional knowledge and skills; Hosseinzadeh et al. 45 reported that medical professional interaction and communication was an instrumental ability for achieving nursing competency and frequently coexisted with insufficient PSE. Better communication skills confer greater PSE among nurses, likely resulting from increased confidence in providing care and constructing positive interpersonal relationships with patients.…”
Section: Discussionmentioning
confidence: 99%
“…CR skills development is facilitated by efficient nursing education, effective nursing management, and professional development of nursing (Hosseinzadeh et al., 2022 ). Evidence shows that CR skills development has significant relationship with the quality of nursing education, professional expertise of nursing instructors, and quality educational environments (Alfayoumi, 2019 ; Forsberg et al., 2014 ; Herron et al., 2016 ; Hunter & Arthur, 2016 ; Oostra et al., 2019 ; Yauri & Nash, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…11,13 However, several studies have shown that the knowledge and practice of nurses regarding ACS were inadequate. 14,15 It was demonstrated that nurses' knowledge and ability to correctly identify the diagnostic finding of patients with ACS was limited. 16,17 Another study conducted in Iran country revealed that nurses have poor knowledge and low critical thinking skills for managing serious conditions in emergency and critical care units.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Another study conducted in Iran country revealed that nurses have poor knowledge and low critical thinking skills for managing serious conditions in emergency and critical care units. 15 Some of the factors affecting nurses' knowledge and necessary practice in caring for patients with ACS include Socio-demographic characteristics such as age, work experience, working department, and educational level, 12,18 health system-related factors such as material resources, human resources, and in-service training, 19 poor knowledge in utilizing clinical guidelines 2 and health system-related barriers including lack of necessary diagnostic and treatment equipment. 20 Inadequate knowledge and poor practice of acute care nurses have a negative impact on patient outcomes.…”
Section: Introductionmentioning
confidence: 99%